The Effect of Organic PGR Application from Mung Bean Sprouts Extract on the Growth of Stem Cuttings of Honey Water Apple Plants (Syzygium aqueum) in Danau Balai Village - Bimo Prasetyo; Khairul Rizal; Fitra Syawal Harahap; Hilwa Walida (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Honey water guava (Syzygium aqueum) is one of the newest high-quality commodities and is increasingly being cultivated by farmers in various regions. This study aimed to evaluate the effects of applying organic plant growth regulators (PGRs) derived from sprout extracts at different doses on the growth of water apple (Syzygium aqueum) plants. A completely randomized design (CRD) with a single treatment factor was employed. The results demonstrated that the 60 mL treatment of ZPT Organic Benefits Extract was the most effective in promoting plant growth, achieving an average height of 10.8 cm and five shoots at 4 weeks after planting (WAP), compared to the control treatment, which reached only 8 cm in height and two shoots. These findings indicate that the 60 mL dose of organic PGR extract from sprouts significantly enhanced growth and stimulated shoot development relative to the other treatments.